Polymer-based nanocomposites: Role of interface for effective microwave absorption. (February 2023) - Wang, Junwei; Sun, Qihui; Li, Jinyao; Guo, Yang; Tian, Wei; Liu, Yifan; Wu, Baoshan; Deng, Longjiang; Mahmood, Nasir; Jian, Xian
Abstract: Polymer-based nanocomposites are playing a key role in advancing microwave absorption and electromagnetic interference shielding technology. Polymer nanocomposites with abundant interfaces are injecting new vitality into the advanced absorbers. Adjustable electrical conductivity, controllable complex permittivity, environmental stability, anti-corrosion, lightweight and facile synthesis process are other key advantages of this system. Therefore, identifying suitable materials to combine with polymers through surface engineering and types of interactions among the dissimilar components are of great importance to achieve strong microwave absorption and guide future trends. This mini-review presents the role of homojunction and heterojunction in polymer-based absorbers. It also discusses how complex heterogeneous and homogenous interfaces influence the corresponding microwave absorption. Then, the challenges with polymer-based absorbers which hinder their electromagnetic shielding properties along with the effective solutions to address these issues are highlighted. In the end, the review provides future direction and strategies to design polymer-based nanocomposites to mitigate microwave pollution at a large scale.